2020
DOI: 10.1088/2399-6528/ab8a68
|View full text |Cite
|
Sign up to set email alerts
|

Viscous dissipation effect on Williamson nanofluid over stretching/shrinking wedge with thermal radiation and chemical reaction

Abstract: This paper scrutinizes the effect of viscous dissipation on unsteady two-dimensional boundary layer flow of Williamson nanofluid over a stretching/Shrinking wedge. To express the boundary condition in concentration problem the passive control concept used. The governing PDEs are converted to ODEs by means of a similarity transformation before being solved numerically by finite difference scheme called Keller-Box method. The equations were numerically solved by using Matlab software 2013a. The characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Available at www.ThermalFluidsCentral.org solution for convective heat and mass transport of a rotating nano-fluid in a vertical conduit, which is bordered by extending and stationary walls. Ibrahim and Negera (2020) investigated the influence of thermal radiation and chemical reaction on the viscous dissipation of Williamson nanofluid over a stretching/shrinking wedge. Khan et al (2020) took into account variable diffusion and conductivity changes in a 3D rotating Williamson fluid flow, as well as the magnetic field and activation energy.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Available at www.ThermalFluidsCentral.org solution for convective heat and mass transport of a rotating nano-fluid in a vertical conduit, which is bordered by extending and stationary walls. Ibrahim and Negera (2020) investigated the influence of thermal radiation and chemical reaction on the viscous dissipation of Williamson nanofluid over a stretching/shrinking wedge. Khan et al (2020) took into account variable diffusion and conductivity changes in a 3D rotating Williamson fluid flow, as well as the magnetic field and activation energy.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…where the prime′ shows the derivative with respect to η, Again by employing the transformations and their partial derivatives in Equation 14, we simplify the boundary conditions in Equations (12) and (13) as follows:…”
Section: Diffusion Equationmentioning
confidence: 99%
“…Some of the recent studies on thermal radiation, heat source, and dissipation effects are indicated in Haile and Awgichew 12 and Ibrahim and Negera. 13 To enhance the working efficiency of manufacturing industries, further understanding on the flow and transport phenomena of electrically conducting fluids is very essential to efficiently design, operate, and regulate modern-day flow systems. To do this, Sakiadis 14 and Crane 15 took the initiative on the study of boundary layer flows of viscous fluids induced by stretching sheet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study shows that higher temperatures obey the generalized Fourier law. Ibrahim and Negera 16 demonstrated the importance of nanofluids with Williamson parameters and used the boundary layer concept to explore the time‐dependent flow of Williamson nanofluids. Their research showed that an increase in Williamson parameters would reduce the heat transmit frequency.…”
Section: Introductionmentioning
confidence: 99%